Collaboration between Immigration and Key Stakeholders in Overseeing National Entry Points - Rahma Dyah Widyaningrum; Fedianty Augustinah; Eny Hartati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to explore the institutional governance and collaboration mechanisms at Indonesia's entry points, emphasising both formal arrangements, such as Memoranda of Understanding, and informal communication channels that facilitate daily operations among Immigration, Customs, Port Authorities, Law Enforcement, and Health Agencies. The research employed qualitative methods, including interviews, observations, and document analysis, grounded in Policy Network theory, to analyse the dynamics of institutional collaboration at entry points. The findings highlight that border oversight effectiveness hinges on inter-agency synergy quality, trust, and the ability to overcome technical and procedural barriers, whilst significant challenges include technological disparity, particularly incompatible data platforms hampering real-time information sharing, and silo mentalities driven by security concerns that impede operational harmonisation, resulting in delays and inefficiencies. Trust mechanisms such as informal communication groups, regular meetings, and leadership support significantly improve coordination and operational performance. The study concludes that sustainable and adaptive governance models characterised by mutual trust, effective communication, and technological integration are essential for enhancing border security and facilitating legal movement. The research underscores the importance of integrating technological systems to ensure interoperability, developing clear cross-agency SOPs, and fostering a collaborative culture that prioritises shared goals over organisational ego. Strengthening institutional collaboration at border crossings will bolster Indonesia's national security, economic growth, and international reputation, and contribute to resilient, efficient border management systems capable of addressing contemporary threats.